History, biography, and the genre of Luke-Acts : an exploration of literary divergence in Greek narrative discourse - Pitts, Andrew W. (Biblical Interpretation Series, 2019)
Unlike contemporary literary-linguistic configurations of genre, current methodologies for the study of the Gospel genre are designed only to target genre similarities not genre differences . This basic oversight results in the convoluted discussion we witness in Lukan genre study today. Each recent treatment of the genre of Luke-Acts represents a distinct effort to draw parallels between Luke-Acts and a specific (or multiple) literary tradition(s). These studies all underestimate the role of literary divergence in genre analysis, leveraging much-if not, all-of their case on literary proximity . This monograph will show how attention to literary divergence from a number of angles may bring resolution to the increasingly complex discussions of the genre(s) of Luke-Acts.